2021
DOI: 10.3390/en14165128
|View full text |Cite
|
Sign up to set email alerts
|

Verifying the Efficiency of a Diesel Particulate Filter Using Particle Counters with Two Different Measurements in Periodic Technical Inspection of Vehicles

Abstract: The article presents the possibility of verifying the efficiency of a diesel particulate filter (DPF) with the use of particle counters using two different measurement methods. The tests were carried out at a vehicle inspection station using a condensation particle counter (CPC) and a diffusion charger (DC). This article presents the results of measurements of 50 vehicles. Removal of the diesel particulate filter from a vehicle is prohibited but is a known phenomenon throughout the EU. The task of periodic tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Both SPN 23 and SPN 10 of V6 low idling emissions were ~10 7 #/cm 3 . This is in agreement with previous studies that reported >10 7 #/cm 3 [47,48] for diesel vehicles without DPF. Note that the reference system measured >3 × 10 6 #/cm 3 so the SPN 23 was probably underestimated.…”
Section: Vehicles Without Particulate Filtersupporting
confidence: 94%
See 1 more Smart Citation
“…Both SPN 23 and SPN 10 of V6 low idling emissions were ~10 7 #/cm 3 . This is in agreement with previous studies that reported >10 7 #/cm 3 [47,48] for diesel vehicles without DPF. Note that the reference system measured >3 × 10 6 #/cm 3 so the SPN 23 was probably underestimated.…”
Section: Vehicles Without Particulate Filtersupporting
confidence: 94%
“…This is one of the first studies that assessed sensors for the PTI of vehicles. Previous studies used prototypes [48][49][50], or the Swiss approved sensor [24]. Here from the six sensors tested, one had the approval (certificate) for the Swiss PTI (Sensor #6), two were prototypes without a specified country for homologation (Sensors #3 and #5), and three sensors (Sensors #1, #2 and #4) had either approval (certificate) for PTI testing or were ready for approval in Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold of the DPF smoke opacity test is very high. Efforts are taking place to add a NO x test, while for DPFs, a much more sensitive particle number methodology will be introduced in the Netherland, Belgium, Germany, and Switzerland [52,53]. However, as most tampering methods are reversible, the user might restore the vehicle before the PTI test.…”
Section: Tampering Availabilitymentioning
confidence: 99%
“…Note that the regulatory limit is 6 × 10 11 #/km (also for particles larger than 23 nm). Typically, vehicles with well-functioning DPF emit at low idling <5 × 10 4 #/cm 3 [18] and with malfunctioning DPF between 10 5 and 10 6 #/cm 3 [19][20][21]. When the DPF is removed or broken >5 × 10 6 #/cm 3 concentrations are expected [20,22,23].…”
Section: Introductionmentioning
confidence: 99%